Pemanfaatan Kecerdasan Buatan Untuk Meningkatkan Kreativitas Dan Literasi Dalam Pembelajaran Bahasa Indonesia Mahasiswa Semester 3 FKIP UNSIKA - Laily Fitria; Rizky Amelia; Alya Safitri Astsaniah; Aulia Sapya; Muhammad Wildan Taftazani; Tata NurLaeily; Bahar Amal (Buletin Pengembangan Perangkat Pembelajaran, 2024)
This study aims to understand student opinions on the role of Artificial Intelligence (AI) in enhancing creativity and literacy in Indonesian language learning. This study involved 25 3rd semester students from the Faculty of Teacher Training and Education, Singaperbangsa University of Karawang, who provided their opinions through a questionnaire. This research method combines quantitative and qualitative approaches, so as to provide a broader and clearer picture. The results describe that most students support the use of AI in learning, especially to enrich vocabulary, stylistic variations, synonyms, and grammar. However, some students were concerned that excessive use of AI could reduce creativity, critical thingking skills and literacy. This research is expected to be a reference for educators in utilizing AI wisely, so that it can provide full benefits without eliminating the important role of lecturers in the teaching and learning process.